EFECTO DE LA SALINIDAD EN EL CRECIMIENTO SALUDABLE DE JUVENILES DE TILAPIA ROJA (Oreochromis mossambicus x Oreochromis niloticus) - DELGADO REVELO, JAVIER ALEXANDER (2023)
The culture of tilapia as a freshwater species can also occur in saline waters, helps sustainable development by avoiding the presence of certain harmful organisms, in addition to reducing stress on the animal. The objective was to evaluate the effect of salinity on the healthy growth of juvenile red tilapia (Oreochromis mossambicus x Oreochromis niloticus) to avoid the incidence of fungi; this research was carried out at the Quevedo State Technical University in the Experimental Campus "La María", in the Aquaculture campus. Red tilapia juveniles weighing 37.02 ± 3.92 g were used, distributed in three treatments with 25 juveniles each and different salt concentrations T1:0 ppm (control treatment), T2:15 ppm and T3:30 ppm respectively, with five replicates organized in plastic tanks. The variables measured were weight gain, mean weight, specific growth rate, absolute growth rate, survival, feed conversion and feed consumption, water parameters and the incidence of fungi in the crop were also controlled. T2 showed higher numerical values in weight gain and absolute growth, these differences were not statistically significant. For feed consumption, there were statistical differences only at 7 days in T1, but thereafter all treatments were statistically identical. The incidence of fungi was higher in T1, which was the control treatment (without the addition of salt), the water and water parameters remained within the optimal range for tilapia.